2019
DOI: 10.1038/s41598-019-53714-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of combination of colistin with fosfomycin or minocycline in a mouse model of multidrug-resistant Acinetobacter baumannii pneumonia

Abstract: Unfortunately, the options for treating multidrug-resistant (MDR) Acinetobacter baumannii (A. baumannii) infections are extremely limited. Recently, fosfomycin and minocycline were newly introduced as a treatment option for MDR A. baumannii infection. Therefore, we investigated the efficacy of the combination of colistin with fosfomycin and minocycline, respectively, as therapeutic options in MDR A. baumannii pneumonia. We examined a carbapenem-resistant A. baumannii isolated from clinical specimens at Severan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…The evolution of E. coli strains is highly determined in the genomic region, and this mechanism [ 5 , 40 , 42 , 43 ]. The virulence APEC genes and the antibiotic-resistant genes are often on the same plasmid [ 44 ], so it potential to be transferred to other E. coli bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of E. coli strains is highly determined in the genomic region, and this mechanism [ 5 , 40 , 42 , 43 ]. The virulence APEC genes and the antibiotic-resistant genes are often on the same plasmid [ 44 ], so it potential to be transferred to other E. coli bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Synergism rates were not unanimous on all studies but was reported in 23/29 papers. Synergisms rate were 100% in 2 in vitro studies against K. pneumoniae [50,71] and 2 in vivo studies respectively against A. baumannii and E.coli [72,73]. The overall effect was indifferent on most isolates of P. aeruginosa and Enterobacterales.…”
Section: Polymyxinsmentioning
confidence: 95%
“…Combination of carbapenem plus colistin seems to be the first option for treatment of MDR-AB infections [33]. In a recent randomized trial comparing colistin alone versus colistin plus meropenem for the treatment of severe infections caused by carbapenem-resistant gramnegative bacteria, the authors concluded that combination therapy was not more efficient than monotherapy and that adding meropenem Many in vitro studies suggested a possible role for intravenous fosfomycin also for the treatment of MDR-AB [13][14][15]. Recently, a fosfomycin-containing regimen showed a more beneficial effect on all-cause mortality, with favorable effectiveness in clinical cure and [16].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed fosfomycin achieved effective concentrations in infected lung tissue [35], and fosfomycin was introduced as a treatment option for infections caused by MDR-AB [36]. In a time-kill study, fosfomycin with colistin showed bactericidal and synergistic effects at 8 h, reducing the bacterial load in the lungs at 48 h compared with monotherapies and the combination of colistin plus minocycline [37]. In another recent study, a combination of colistin and fosfomycin had significantly better microbiologic responses with trends toward more favorable treatment outcomes and lower mortality compared with those treated with colistin alone [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation